DIFFERENCES BETWEEN LEVEL TRAJECTORY AND ACADEMIC PERFORMANCE WITH EMOTIONAL SKILLS IN UNIVERSITY STUDENTS - Andrade, Norma Angelica Ortega; Ramirez, Mucio Alejandro Romero; Guerrero, Ana Maria Rivera (European Scientific Journal, ESJ, 2014)
Emotional intelligence is involved in the recognition process, use, understanding and management of its own and others’ emotional statesto resolve emotional problems and regulate behavior (Salovey, Brackett & Mayer, 2004). Emotional intelligence is taken up in this research, based in Salovey and Mayers´s model (1990), to identify whether there were significant differences in emotional skills of students from health sciences, as a function of level of school trajectory and academic performance. 300 university students were included from three disciplines of the Institute of Health Science at the Autonomous University of the State of Hidalgo, México. The sample was selected based on a non-probabilistic sample by subjects type (García, 2009). Three instruments were administered to evaluate emotional understanding, perception and expression. A nonparametric analysis with Chi Square (X²), did not detect differences statistically significant among students as a function of academic performance and levels of school trajectory for the three abilities of emotional understanding, expression and perception. Only subtest variable score for individuals emotional ability for emotion labeled love, sadness, happiness, anger and fear were related to the independent variables of academic performance and levels of school trajectory.